Astrocytes in intracerebral hemorrhage: impact and therapeutic objectives - Dong, Hao; Wen, Xin; Zhang, Bai-Wen; Wu, Zhe; Zou, Wei (Frontiers in Molecular Neuroscience, 2024)
Intracerebral hemorrhage (ICH) manifests precipitously and profoundly impairs the neurological function in patients who are affected. The etiology of subsequent injury post-ICH is multifaceted, characterized by the intricate interplay of various factors, rendering therapeutic interventions challenging. Astrocytes, a distinct class of glial cells, interact with neurons and microglia, and are implicated in a series of pathophysiological alterations following ICH. A comprehensive examination of the functions and mechanisms associated with astrocytic proteins may shed light on the role of astrocytes in ICH pathology and proffer innovative therapeutic avenues for ICH management.